UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI IPS 1 PADA MATA PELAJARAN GEOGRAFI MELALUI METODE STUDI KASUS DI SMA NEGERI 1 JATIBARANG KABUPATEN BREBES - Agitawardhani, Wisnu; Bramasta, Dhi; Mustolikh, Mustolikh (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This Classroom Action Research is motivated by the low motivation of students in the Geography learning process. This can be seen during learning activities, most students are less enthusiastic in learning activities due to various factors, namely: students tend to get bored following lessons, students lack mastery of the material, and so on. This Classroom Action Research aims to increase students' learning motivation in geography subject of eleven social studies one senior high school one Jatibarang Brebes through case study learning model. This research is a class action research conducted in 2 cycles. Each cycle consists of 2 meetings, each meeting consists of 2 lesson hours. The implementation planning of each cycle includes planning, action implementation, observation, and reflection. Data collection used observation, questionnaire, interview, and documentation techniques. The research subjects were students of class eleven social studies one senior high school one Jatibarang which amounted to 35 people. The results of this study indicate that the case study learning method that has been carried out can increase student learning motivation in Geography learning. This can be seen from the overall score of student learning motivation before the action of 40.91% included in the low category, cycle I of 52.74% included in the medium category. Then in cycle II it increased again to 63.25% including in the high category. So it can be said that the actions that have been taken are in accordance with what is expected.